2018
DOI: 10.12816/0046999
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Risk Factors of Visual Impairment in Type 2 Diabetes Mellitus at King Hussein Medical Center

Abstract: Objectives: To investigate the causes of severe visual impairment among Jordanians with type II diabetes mellitus and its associated systemic factors. . After getting the ethical approval and taking a consent form, all patients with type II diabetes mellitus who attended the medical retina clinic in the ophthalmology department and found to have best corrected visual acuity (BCVA) of less than 6/12 in the best eye were included in the study. The patients were subjected to detailed ophthalmic exam including bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Diabetic patients with duration of 5 or more years were 3.7 times more likely to be visually impaired compared to diabetics with duration of below 5 years. This finding was similar to previous studies in Denmark (Siersma et al, 2019), Jordan (Khatatbeh et al, 2018), Pakistan (Shehzad et al, 2020), and Tunisia (Kahloun et al, 2014), which demonstrated that longer duration of diabetes had a significant association with the occurrence of visual impairment. With an increase in the span of diabetes, there is a high chance of developing ocular comorbidities such as advanced diabetic retinopathy and neovascular glaucoma, which, in turn, leads to severe visual impairment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Diabetic patients with duration of 5 or more years were 3.7 times more likely to be visually impaired compared to diabetics with duration of below 5 years. This finding was similar to previous studies in Denmark (Siersma et al, 2019), Jordan (Khatatbeh et al, 2018), Pakistan (Shehzad et al, 2020), and Tunisia (Kahloun et al, 2014), which demonstrated that longer duration of diabetes had a significant association with the occurrence of visual impairment. With an increase in the span of diabetes, there is a high chance of developing ocular comorbidities such as advanced diabetic retinopathy and neovascular glaucoma, which, in turn, leads to severe visual impairment.…”
Section: Discussionsupporting
confidence: 92%
“…The most prevalent causes of visual impairment in diabetic patients are cataract, diabetic retinopathy, refractive error, glaucoma, and other ocular conditions (e.g., epiretinal membrane, corneal opacity, and age-related maculopathy) (Mabaso & Oduntan, 2014; Onakpoya et al, 2016; Seba et al, 2015; Shehzad et al, 2020, Wen et al, 2020). The possible risk factors for the occurrence of visual impairment among diabetic patients are older age, longer duration of diabetes, body mass index (BMI), hypertension, heart disease, peripheral neuropathy, and renal failure (Kahloun et al, 2014; Khatatbeh et al, 2018; Shehzad et al, 2020; Siersma et al, 2019; Zhang et al, 2008).…”
mentioning
confidence: 99%